A Methodological Review on Challenges in Big Data Environment - Singh, Manpreet; Yadav, Rimmy; Ram, Balwinder (IJRDO -Journal of Computer Science Engineering, 2017)
Big data has shown the great potential in optimizing, making decisions, spottingbusiness trends in various fields such as manufacturing, finance, Information Technology. Thispaper provides a multi- disciplinary overview of the research issues in big data and itstechniques, tools and framework related to the privacy , data storage management, network andenergy consumption, fault tolerance and data visualizations. Besides this, outcome challengesand opportunities available in this big data platform have made.